Oxford international primary english workbook for grade 3 - Barber, Alison (Karachi: Oxford university Press., 2022)
The Oxford International Primary English Workbook for Grade 3 complements the Student Book by providing hands-on practice and reinforcement of key language skills. Through a variety of exercises, students focus on improving their reading comprehension, grammar, punctuation, and writing abilities. The workbook includes activities that promote critical thinking, vocabulary development, and the application of language concepts learned in the classroom. Designed to enhance student engagement and confidence, it supports independent learning with a structured approach, offering additional practice in areas like spelling, sentence formation, and understanding different text types.